Developing Moral Theology Learning Strategy to Improve Student Achievement - Didin Sirojudin; Taufik Eko Yulianto (SCHOOLAR: Social and Literature Study in Education, 2021)
Strategy is a method or series of systematic actions taken to achieve learning objectives so that they can run effectively and efficiently. In the Akidah Akhlak learning process the strategies used are still not optimal, which is marked by students paying less attention when the teacher explains the material, low interest in learning and decreasing student learning outcomes. So we need the right strategy to overcome it. This type of research is a qualitative and descriptive research that the researchers conducted at MTsN 3 Jombang School. The purpose of this study was to find out how the teacher's strategy in improving the learning of Akidah Akhlak at MTsN 3 Jombang. The data obtained through several methods, namely the interview, observation, and documentation methods, to facilitate data analysis, then interpreted by means of inductive thinking, is based on special knowledge after which a general solution is taken, resulting in conclusions that can be accounted for. Based on the results of the analysis of observational data, interviews and documentation obtained by the researchers, it can be concluded that the Teacher's Strategy in Improving Moral Moral Learning at MTsN 3 Jombang uses various approaches, methods and learning media to improve the quality of Akidah Akhlak learning, therefore using primary data and secondary data obtained through interviews with core informants, and ordinary informants as well as repeated observations about Akidah Akhlak learning. The strategy used is to approach students which aims to determine the characteristics and learning styles of students, then use learning methods and more varied learning media when teaching.